2012
DOI: 10.21829/azm.2012.282838
|View full text |Cite
|
Sign up to set email alerts
|

The life cycle of a desert spider inferred from observed size frequency distribution

Abstract: We studied the life cycle of the spider Syspira tigrina (Araneae: Miturgidae) by indirect methods. This species is endemic to the North American deserts and locally abundant; nevertheless, information on its biology is scarce. We did monthly collections for over a year at La Paz, Baja California Sur, Mexico. We found that adult spiders were more abundant between August and November 2005 and had low abundance or were absent the remainder of the year while juveniles were present all year. To estimate changing bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Considering the fact that male spiders reach maturity faster than females, Romero & Vasconsellos-Neto (2005) observed that female spiders are more frequently observed during adult and sub-adult stages while male spiders are frequent during the juvenile stage. High number of collected adults were observed since female spiders oviposit throughout the entire year (Nieto-Castañeda et al, 2012). Female spiders typically ders.…”
Section: Biodiversity Indicesmentioning
confidence: 99%
“…Considering the fact that male spiders reach maturity faster than females, Romero & Vasconsellos-Neto (2005) observed that female spiders are more frequently observed during adult and sub-adult stages while male spiders are frequent during the juvenile stage. High number of collected adults were observed since female spiders oviposit throughout the entire year (Nieto-Castañeda et al, 2012). Female spiders typically ders.…”
Section: Biodiversity Indicesmentioning
confidence: 99%
“…The phenology of an organism is understood as the temporal variations in the life cycle of the individual (Menzel 2002;Romero and Vasconcellos-Neto 2003), and serves as an important aspect to understanding the population dynamics of a species (Wolda 1988). In spiders, the term phenology has been applied commonly to the study of variations in the age structure of populations (Romero and Vasconcellos-Neto 2003;Villanueva-Bonilla and Vasconcellos-Neto 2016) and to describe the life cycle of individuals (Nieto-Castañeda et al 2012). Tretzel (1954) and Paquin and Dupérré (2001) argue that spiders may have four phenological patterns based on the reproductive period of the population as determined by the peak abundance of adult males.…”
Section: Introductionmentioning
confidence: 99%
“…Otro aspecto que resalta de las arañas de este género es que poseen ciclos de vida muy peculiares, ya que presentan un solapamiento muy marcado en tallas corporales de diferentes estadios, resultado quizá de las diferentes tasas de crecimiento y el continuo reclutamiento de estos organismos, producto de ovoposición de las hembras durante todo el año. Estos patrones no han sido registrados para otras especies de arañas en las que han sido estudiados sus ciclos de vida (Nieto-Castañeda, Salgado-Ugarte y Jiménez, 2012).…”
Section: Introductionunclassified